Fundamentals of Physics Extended (10th Edition)

Published by Wiley
ISBN 10: 1-11823-072-8
ISBN 13: 978-1-11823-072-5

Chapter 34 - Images - Problems - Page 1039: 17e



Work Step by Step

Using the lens equation of $$\frac{1}{f}=\frac{1}{p}+\frac{1}{i}$$ solving for $i$ yields $$\frac{p}{pf}-\frac{f}{pf}=\frac{1}{i}$$ $$\frac{p-f}{pf}=\frac{1}{i}$$ $$i=\frac{pf}{p-f}$$ Substituting known values of$f=20cm$ and $p=10cm$ yields $$i=\frac{(10cm)(20cm)}{10cm-20cm}=-20cm$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.